Penguatan Keterampilan Praktik Mahasiswa Kebidanan melalui Uji Kelayakan dan Pemanfaatan SMARTHOM (Simulator Persalinan) di Laboratorium Universitas Faletehan - Feling Polwandari; Dewi Rahmawati; Muchamad Fajar Arifin; Sita Aulia Adzani; Rindiani Rindiani; Kaila Amatul Azhar; Dendi Pratama Riawan (BADAN PENERBIT STIEPARI PRESS, 2026)
Learning Midwifery practice learning requires media that closely resemble real conditions so that students can optimally develop their clinical skills. The innovation of the SMARTHOM (Smart Phantom) device was developed as a labor delivery simulator based on electromechanical systems and the Internet of Things (IoT), designed to enhance the learning experience in the laboratory. The aim of this study was to determine the feasibility level of the SMARTHOM device as a learning medium for childbirth simulation among midwifery students. This research employed a descriptive approach with a trial method involving 15 midwifery students from Faletehan University. The instrument used was the System Usability Scale (SUS) to assess user satisfaction and ease of use of both the application and the simulator device. The results showed an average score of 84.3, which falls under the “highly feasible” category. The highest-rated aspects included ease of use and the functional suitability of the device with the stages of the childbirth process. Overall, the findings indicate that SMARTHOM is effective as a midwifery laboratory learning medium and has great potential for further development into interactive digital learning.